STRATEGI MALAYSIA DALAM MENINGKATKAN WISATAWAN INDONESIA MELALUI SLOGAN “MALAYSIA TRULY ASIA” SEBAGAI NATIONAL BRANDING PADA TAHUN 2013 - 2014 - Putri, Adina Tria; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study discusses how a slogan to become National Branding can affect the number of foreign tourists, especially those implemented by the State of Malaysia, namely